Determination of iron in drinking water after its flotation concentration by two new dithiocarbamate collectors - Pavlovska, Gorica; Stafilov, Trajče; Čundeva, Katarina (My University, 2015)
Two new methods for the determination of iron by atomic absorption spectrometry (AAS) are proposed for drinking water. The determination was made after flotation concentration of Fe by using of two new flotation collectors: lead(II) heptyldithiocarbamate, Pb(HpDTC)2 and cobalt(III) heptyldithiocarbamate Co(HpDTC)3. All important parameters for the two proposed procedures were optimised (pH, mass of Pb, mass of Co, amount of HpDTC(-), type of surfactant, induction time, etc.). Flotation recovery (R) of Fe was very high (from 94.4 to 104.4%) for the two proposed procedures. The detection limit of the methods was 2.17 μg L(-1) for Pb(HpDTC)2 and 2.39 μg L(-1) for Co(HpDTC)3, respectively. The proposed methods have been applied for the analysis of five samples of drinking water. The acquired AAS results for Fe by both new methods were compared with those obtained by inductively coupled plasma-atomic emission spectrometry (AES-ICP). It is shown that they are in good agreement. The results are also confirmed by the method of standard additions.